The way they were : how epic battles and bruised egos brought a classic Hollywood love story to the screen - Hofler, Robert (Citadel Press, Kensington Publishing Corp., 2023)
"Coinciding with the 50th anniversary of "The Way We Were," this intriguing and impeccably researched book is the first ever account of the making of the classic film starring Barbara Streisand and Robert Redford, revealing the full story behind its genesis and continued controversies, its many deleted scenes, its much-anticipated but never-filmed sequel, and the real-life romance that inspired this groundbreaking love story"--